Distributed Energy Conserving Scheme for Residential WSN based on Behaviour of Utilization (BoU) - Dhakshayeni, PA; Meenakshi, S (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks (WSNs) is a composition of tiny self-operated devices that communicate with other devices in an ad-hoc fashion. WSNs find its application in real-time appliances due to its cost effectiveness and ease of deployment nature. Energy preserving in these networks while extending its support for real-time appliances is vital so as to preserve the operating hours of the system. To perform an energy efficient operation of WSN devices integrated with real-time appliances, a mutually cooperative and monitoring model is preferred. Depending on the Behavior of Utilization (BoU), energy allocated for each appliance can be shared in a distributed manner with the other appliances to cope-up with the energy constraints and improve prolonged operation. With forehand information about the operating device and its nature towards energy requirement, the energy allocation can be decided over a multi-state operative function to make a decision. The decision making follows Markov-Chain Model (MM) to make decisions between the operation states of an appliance. The outcome of the decision model will result in admitted operation time and energy conservation of an appliance.Â Â